Caracterização das dimensões da aresta lateral de corte e do núcleo dos instrumentos Mtwo®, ProTaper®, Wizard Navigator® e BioRace® - Brito, Ana Paula Pedroso (2015)
Purpose: to determine flute-to-shank ratio of rotatory nickel-titanium instruments Mtwo® #30/.05, ProTaper® #30/.09, Wizard Navigator® #30/.06 and BioRace® 35/.04. Material and methods: Instruments’ diameter were measured with a digital caliper in the first five flutes and abraded longitudinally by a diamond disk until instrument half diameter was achieved in flutes region. The samples were then fixed in stubs and SEM images were performed at 60X magnification. The flutes and shanks areas were measured, and flute-toshank ratio was achieved using software AxioVision®. Statistical analysis was performed by ANOVA and Tukey’s Test for comparison between groups. Results: There was significant statistical difference for flutes areas. Mtwo® #30/.05 had the higher shank areas and was significantly different from the other instruments, except for Wizard Navigator #30/.06 ate the second flute site. Flute-to-shank ratio showed a 3-28% variation. Conclusions: Flutes dimensions were lower than shanks’. Wizard Navigator® #30/.05 had lower flute-to-shank ratio than other files.